There goes the neighborhood? People's attitudes and the effects of immigration to Australia - Mathias Sinning; Matthias Vorell (Institute for the Study of Labor (IZA), 2011)
This paper compares the effects of immigration flows on economic outcomes and crime levels to the public opinion about these effects using individual and regional data for Australia. We employ an instrumental variables strategy to account for non-random location choices of immigrants and find that immigration has no adverse effects on regional unemployment rates, median incomes, or crime levels. This result is in line with the economic effects that people typically expect but does not confirm the public opinion about the contribution of immigration to higher crime levels, suggesting that Australians overestimate the effect of immigration on crime.
urn:nbn:de:101:1-201108093121
Keywords: F22; J61; 330; international migration; effects of immigration; attitudes towards immigrants